RELATIONSHIP BETWEEN PERIODONTAL DISEASES AND MENTAL HEALTH: A NARRATIVE REVIEW - Mariana O. Levkiv; Pavlo Yu. Ostrovskyi; Svitlana I. Boitsaniuk (Клінічна та профілактична медицина, 2025)
Introduction. Periodontal diseases are prevalent oral diseases affecting the global population. These diseases arise from infections and inflammation of the gums and supporting bones, significantly impacting oral health. The established link between periodontal and systemic diseases underscores their importance as a public health concern. Chronic stress and depression can result in general dysregulation of the immune system, of both cellular and humoral pathways, which may contribute to pathogenic infection and concomitant periodontal tissue destruction.